Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.4993/acrt.24.47
|View full text |Cite
|
Sign up to set email alerts
|

Successful alectinib treatment for a mechanically ventilated patient with <i>ALK</i>-positive non-small cell lung cancer

Abstract: We report a 38-year-old man with poor performance status (PS) who was diagnosed as stage IV non-small cell lung cancer (NSCLC) harboring the echinoderm microtubule-associated protein like 4 (EML4)-anaplastic lymphoma kinase (ALK) fusion gene. Crizotinib, an ALK inhibitor, was administered after a temporary effect of combination cytotoxic chemotherapy. Chest computed tomography showed air space consolidations and diffuse ground glass opacities in the both lungs after 5 days of treatment with crizotinib, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Review of agents found 36 (31%) with guidance for alternative routes of administration readily available in tertiary resources or commercial liquid formulations, 38 (33%) with off‐label manufacturer information or case reports describing manipulation of solid dosage formulations, and 42 (36%) with no data or insight limited to pharmacokinetic studies. Findings are detailed in Table 3 10‐196 . Unique administration instructions (ie, with or without foo...…”
Section: Resultsmentioning
confidence: 99%
“…Review of agents found 36 (31%) with guidance for alternative routes of administration readily available in tertiary resources or commercial liquid formulations, 38 (33%) with off‐label manufacturer information or case reports describing manipulation of solid dosage formulations, and 42 (36%) with no data or insight limited to pharmacokinetic studies. Findings are detailed in Table 3 10‐196 . Unique administration instructions (ie, with or without foo...…”
Section: Resultsmentioning
confidence: 99%
“…Two additional case reports demonstrated continued response to therapy without adverse effects. 17,18 The reports used a water-based and non-specified recipe, respectively. Both preparations were administered via NG tube, with one report utilizing a PEG tube as well.…”
Section: Discussionmentioning
confidence: 99%